Perceiving The Importance Of Job-Related Skills In The 4th Industrial Revolution Era From The Perspectives Of Graduates And Employers - Getrude C. Ah Gang @ Grace; Shazia Iqbal Hashmi; Chua Bee Seok (2020 SERSC, 2020)
This study focuses on a comparing the perceptions of the importance of seven job-related skills (intrapersonal, interpersonal, computing, entrepreneurship, management, personal organization & leadership) between graduates and employers. These include the four job-related skills emphasized in the 4th Revolution Industry (i.e. communication, critical thinking, creativity, & collaboration). We also compared 17 interview attributes provided in the graduates ’curriculum vitae perceive to be important by both graduates and employers. A total of 279 graduates and 102 employers participated in this study. We predicted there would be a gap between the two parties in how they perceive the importance of each jobrelated skill and job-characteristic. A set of questions divided into four sections was used to measure the variables. These sections are Part A: Demographic variables; Part B: Seven Job-related skills (adapting employability-related questions from Goldsmith’s soft skills inventory); Part C: Four job-related skills based on the 4C’s in the Fourth Industrial Revolution (communication, critical thinking, creativity, & collaboration), and Part D: The 17 interview attributes for the job screening process. The study only revealed that employers perceived three interview attributes (i.e. internship, studying abroad and cocurricular activities) as more important predictors of success in the job screening process. These findings may increase awareness among both universities and graduates of the importance of the three factors emphasised by employers in the job screening process. Universities and relevant authorities should encourage students to be actively involved in co-curricular activities, internships and outbound mobility. This may result in more balanced graduates who can meet the demands of industry.